Peningkatan Minat Belajar IPA Menggunakan Website Html 5 Siswa Kelas IV SDN Degung - Yusuf Bahtiyar; Nadziroh; Tyas Ayu Sophiany (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
This study aims to find out that the use of a website (interactive HTML5) can increase interest in online science learning in 4th grade students of SD Negeri Degung for the 2020/2021 academic year. This research is a type of classroom action research with a continuous cycle model. The research subjects were the 4th grade students of SD Negeri Degung, totaling 10 students. The object of the research is to increase interest in learning science online through the use of website (interactive HTML5). Collecting data through the results of observations and questionnaires. Analysis of the data used is the analysis of observation of learning interest. The results showed that the use of the website (interactive HTML5) can increase the interest in learning science online in grade 4 SD Negeri Degung. The success indicator in this study is 75%. In this study, there was an increase in interest in learning science online from pre-action to cycle I by 20.5% and in cycle I to cycle II by 11%. This study concludes that the use of a website (interactive HTML5) can increase interest in learning science online for 4th grade students of SD Negeri Degung for the 2020/2021 academic year. The use of the website can be a reference for other schools to increase student interest in learning during the pandemic.